Cases and materials on creditors' rights - MacGuigan, Mark, 1931-1998 (Book collections on Project MUSE., 1967)
This book is a detailed study of the debtor-creditor relationship, with particular attention to the position of the unsecured creditor. In these times of "credit-existence" this account is an important source of information for those in the field of law, economy, politics, and business